Effects of light spectra and 15N pulses on growth, leaf morphology, physiology, and internal nitrogen cycling in Quercus variabilis Blume seedlings - Gao, Jun; Zhang, Jinsong; He, Chunxia; Wang, Qirui (PLOS ONE, 2021)
Light spectra of sunlight transmittance can generate an interactive effect with deposited nitrogen (N) on regenerated plants across varied shading conditions. Total N content in understory plants can be accounted for by both exogeneous and endogenous sources of derived N, but knowledge about the response of inner N cycling to interactive light and N input effects is unclear. We conducted a bioassay on Chinese cork oak ( Quercus variabilis Blume) seedlings subjected to five-month N pulsing with 15 NH 4 Cl (10.39 atom %) at 120 mg 15 N plant -1 under the blue (48.5% blue, 33.7% green, and 17.8% red), red (14.6% blue, 71.7% red, 13.7% green), and green (17.4% blue, 26.2% red, 56.4% green) lighting-spectra. Half of the seedlings were fed twice a week using a 250 ppm N solution with micro-nutrients, while the other half just received distilled water. Two factors showed no interaction and neither affected growth and morphology. Compared to the red-light spectrum, that in blue light increased chlorophyll and soluble protein contents and glutamine synthetase (GS) activity, root N concentration, and N derived from the pulses. The green-light spectrum induced more biomass allocation to roots and a higher percentage of N derived from internal reserves compared to the red-light spectrum. The 15 N pulses reduced the reliance on N remobilization from acorns but strengthened shoot biomass, chlorophyll content, GS activity, and N concentration. In conclusion, light spectrum imposed an independent force from external N pulse to modify the proportion of N derived from internal sources in total N content in juvenile Q . variabilis .